Belief into Action Scale: psychometric properties of the Farsi version - Hafizi, Sina (Mental health, religion & culture, 2016)
This study assessed the psychometric properties of the Farsi version of Belief into Action Scale (FaBIAC) in a sample of healthy volunteer Muslims. A convenience sample of 200 healthy volunteer was enrolled from Tehran, Iran. Using a standard forward-backward method, we translated the English version of the BIAC into Farsi. Internal consistency and test-retest reliability of the measure were assessed by Cronbach’s alpha and intraclass correlation coefficient. Convergent validity of the measure was assessed by examining the association between FaBIAC score and Hoge Intrinsic Religiosity Scale score. Divergent validity was assessed by evaluating the association between FaBIAC score and measures of perceived stress, depression, and social support. The findings of this study, while preliminary, suggest that the FaBIAC is a reliable and valid measure of religious commitment and can be used in studies of Farsi-language Muslim populations.